BaTiO3 platelets and poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) hybrid composites for energy storage application. (August 2018) - Lv, Xuguang; Luo, Hang; Chen, Sheng; Han, Xianghui; Ma, Chao; Zhou, Xuefan; Liu, Weiwei; Wu, Zhong; Zhou, Kechao; Zhang, Dou
Graphical abstract: Polymer nanocomposites containing modified BaTiO3 platelets with a novel fluoro-polymer produced the high discharged energy density at the low electric field. Highlights: BaTiO3 platelets were prepared for energy storage application. A novel fluoro-polymer was designed to engineer the surface of BaTiO3 platelets. The discharge energy density of the composite was increased to 1.27 J/cm3 at 60 kV/mm. Abstract: In this paper, BaTiO3 platelets are utilized for the first time to incorporate into polymer matrix for energy storage. To improve the dispersibility and compatibility of the BaTiO3 platelets in the composites, a new type of fluoro-polymer poly2, 5-bis[(2, 3, 5, 6-tetrafluoro-4-trifluoromethyl)oxycarbonyl]styrene (PM7F) was designed for the first time to engineer the surface of BaTiO3 platelets by surface-initiated reversible-addition-fragmentation chain transfer polymerization method. Each structural unit in the molecular chain of this novel modifier contained 14 fluorine atoms, resulting in effectively decreasing the surface energy of BaTiO3 platelets. As a result, the BaTiO3 platelets modified by PM7F were homogeneously dispersed in the polymer poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (P(VDF-TrFE-CTFE)) matrix. The permittivities of the nanocomposites were significantly improved compared with the pure polymer matrix. The energy storage density of the nanocomposites was largely enhanced by adding the BaTiO3 platelets. The discharged energy density of the nanocomposite with 15 vol% BaTiO3 platelets was 1.26 J/cm 3, which was nearly double to that of pure P(VDF-TrFE-CTFE) (0.64 J/cm 3 ) at the same electric field (60 kV/mm). The findings provide an effective modifier and a new routine for high performance capacitors.